Symposium 3: Tomorrow’s Networked Posthumans: Reflections on Artificial Intelligence and the Digital Well-Being of Young Children - Adams, Catherine; Groten, Sean; Yin, Yin (Proceedings of the International Conference on Networked Learning, 2024)
While networked learning (NL) is most often associated with adult learning and professional work practices, examining the “ontogenetic development” of children in the context of today’s smart global networks is also relevant to NL research (Rodríguez-Illera & Barberà in NLEC et al., 2021). In this paper, we ask: What child-technology relations are being forged in our posthuman era of Artificial Intelligence (AI), big data and global networks? We begin by scoping the intensifying presence of networked, smart technologies in the home life of infants, toddlers and preschoolers; we examine recent policy frameworks regarding AI, ethics and children. We then turn to two phenomenological philosophers, Michel Serres and Bernard Stiegler to consider how their thinking about digital technologies might provide insight for parents and educators as they endeavour to make the best “smart” technology choices for children. Finally, we consider the implications of our phenomenological reflections on today’s young posthumans for networked learning and postdigital education.